2014
DOI: 10.4168/aair.2014.6.2.126
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inhaled Albuterol in Transient Tachypnea of the Newborn

Abstract: PurposeTransient tachypnea of the newborn (TTN) is a disorder caused by the delayed clearance of fetal alveolar fluid. β-adrenergic agonists such as albuterol (salbutamol) are known to catalyze lung fluid absorption. This study examined whether inhalational salbutamol therapy could improve clinical symptoms in TTN. Additional endpoints included the diagnostic and therapeutic efficacy of salbutamol as well as its overall safety.MethodsFrom January 2010 through December 2010, we conducted a prospective study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…At the second stage analysis, by exclusion of the retraction scores less than 2 we accomplished our primary objective compatible to the similar studies. In a study in Korea, Myo-Jing Kim et al indicated that the duration of supplemental oxygen therapy and empiric antibiotic therapy were significantly shorter in the salbutamol group but there was no significant difference in duration of tachypnea before 72 hours of admission and duration of hospitalization (23).…”
Section: Discussionmentioning
confidence: 99%
“…At the second stage analysis, by exclusion of the retraction scores less than 2 we accomplished our primary objective compatible to the similar studies. In a study in Korea, Myo-Jing Kim et al indicated that the duration of supplemental oxygen therapy and empiric antibiotic therapy were significantly shorter in the salbutamol group but there was no significant difference in duration of tachypnea before 72 hours of admission and duration of hospitalization (23).…”
Section: Discussionmentioning
confidence: 99%
“…Infants with transient tachypnea of the newborn were characterized based on the following clinical criteria: 1) At least 35 weeks gestational age, 2) presence of respiratory distress less than 6 hours after birth (respiratory rate more than 60/min, cyanosis, grunting, nasal flaring, or retraction), and 3) typical chest radiography findings (fluid in minor fissures, hyperinflation, prominent vascular/perihilar markers) (11).…”
Section: Subjectsmentioning
confidence: 99%
“…This is in contrast to results observed by Armangil D et al 10 which showed significant decrease in respiratory rate (70±19 vs 62±14) and by Venkatamurthy et al 11 respiratory rate was (75.74±5.93 and 66.31±7.41) before and after nebulization respectively. Myo Jing Kim et al 12 showed that there was decrease in the duration of tachypnea after treatment with salbutamol nebulization than in the control group (31.3±23.7 h vs. 53.5±56.8 h, respectively); but this difference was not significant (P=0.37). However, no differences in the maximum respiratory rates during the acute period after inhalation treatment were observed between the salbutamol inhalation group and the control group.…”
Section: Clinical Characteristicsmentioning
confidence: 73%